2008
DOI: 10.4314/afrrev.v2i3.41073
|View full text |Cite
|
Sign up to set email alerts
|

Yield Performance of Some Cowpea Varieties under Sole and Intercropping with Maize at Bauchi, Nigeria.

Abstract: Field experiments were conducted during the 1997 and 1998 are more suitable for high yield in Bauchi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
4
2
0
Order By: Relevance
“…The narrow spacing in intercrop 2 resulted in high cowpea plant density and hence competit ion for growth resources. This is consistent with the findings of Ofori and Stern [18] and Alhaji [36] who observed reduction in cowpea yield due to high maize density in the intercropping system. Studies conducted by Agricultural Research Division [29] also reported that intercropping reduced the yield of cowpea.…”
Section: Resultssupporting
confidence: 82%
“…The narrow spacing in intercrop 2 resulted in high cowpea plant density and hence competit ion for growth resources. This is consistent with the findings of Ofori and Stern [18] and Alhaji [36] who observed reduction in cowpea yield due to high maize density in the intercropping system. Studies conducted by Agricultural Research Division [29] also reported that intercropping reduced the yield of cowpea.…”
Section: Resultssupporting
confidence: 82%
“…Therefore values directly influences grain yield of cowpea. Number vof pods plant -1 of cowpea were higher in monoculture as compared to (Alhaji, 2008). This results are also parallel to the findings of Geren et al (2007).…”
Section: Resultssupporting
confidence: 87%
“…The grain yield of cowpea is higher when intercropped with the ratio of one row maize to one row cowpea 1033.77 kg ha -1 followed by one row maize to two-row cowpea 568.63 kg ha -1 (Table 2). This is consistent with the findings of Alhaji (2008) he observed reduction in cowpea yield due to high maize density in the intercropping system. Chemeda (1997) reported higher grain yield under sole cowpea compared to intercropping.…”
Section: Effect Of Intercropped Cowpea With Maize On Plant Height Number Of Pod Per Plant Number Of Seed Per Pod Grain Yield and Total Bisupporting
confidence: 92%